1990
DOI: 10.1111/j.1476-5381.1990.tb12977.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gastric mucosal integrity by endogenous nitric oxide: interactions with prostanoids and sensory neuropeptides in the rat

Abstract: The interactions between nitric oxide (NO), prostacyclin and sensory neuropeptides in the maintenance of gastric mucosal integrity have been investigated in the anaesthetized rat. Administration of either NG‐monomethyl‐l‐arginine (l‐NMMA) to inhibit endothelium‐derived NO formation, indomethacin to inhibit prostanoid biosynthesis or chronic capsaicin pretreatment to deplete sensory neuropeptides, did not induce acute mucosal injury. In capsaicin‐pretreated rats, however, l‐NMMA (12.5–100 mg kg−1 i.v.) dose‐dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
189
0
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(210 citation statements)
references
References 34 publications
15
189
0
3
Order By: Relevance
“…Several studies have demonstrated the importance of endogenous NO in the protection of gastric mucosa (Kim and Kim, 1998;Tanaka et al, 2001;Whittle et al, 1990). Also endothelial NO plays an important role in the modulation of gastric mucosal integrity by interacting with sensory neuropeptides (Whittle et al, 1990;Tepperman and Whittle, 1992), reducing neutrophil adhesion and increasing gastric blood flow and mucus secretion (Souza et al, 2004). In the present study, alcohol significantly reduced gastric mucosal NO level with increase mucosal injury compared to control group.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Several studies have demonstrated the importance of endogenous NO in the protection of gastric mucosa (Kim and Kim, 1998;Tanaka et al, 2001;Whittle et al, 1990). Also endothelial NO plays an important role in the modulation of gastric mucosal integrity by interacting with sensory neuropeptides (Whittle et al, 1990;Tepperman and Whittle, 1992), reducing neutrophil adhesion and increasing gastric blood flow and mucus secretion (Souza et al, 2004). In the present study, alcohol significantly reduced gastric mucosal NO level with increase mucosal injury compared to control group.…”
Section: Discussionsupporting
confidence: 52%
“…These findings suggest that endogenous NO may participate in the regulation of gastric secretion via an intracellular signaling molecule (Dijkstra et al, 2004). Several studies have demonstrated the importance of endogenous NO in the protection of gastric mucosa (Kim and Kim, 1998;Tanaka et al, 2001;Whittle et al, 1990). Also endothelial NO plays an important role in the modulation of gastric mucosal integrity by interacting with sensory neuropeptides (Whittle et al, 1990;Tepperman and Whittle, 1992), reducing neutrophil adhesion and increasing gastric blood flow and mucus secretion (Souza et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Among these patterns, NO-mediated regulation is particularly important as it is associated with host defense and inflammatory responses (26) and also plays a pivotal role in gastric mucosal protection against damage induced by ethanol, stress, endotoxins and drugs (27). NOS activity is particularly high in gastric tissues (28), where NO helps maintain gastric tissue integrity (29), controls gastromucosal-derived blood flow (30) and increases gastric mucus synthesis and secretion (28). L-arginine, a NOS substrate, has been shown to facilitate gastric ulcer healing by increasing cell regeneration in stomach tissues (31).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the NO system beside playing a role in the regulation of the gastric mucosal blood¯ow which contributes to protection against injurious agents (Sorbye & Svanes, 1994), cooperates with the prostaglandin system in the maintenance of gastric mucosal integrity (Whittle et al, 1990). Furthermore these two mediators can regulate the synthesis of one another as NO has been shown to stimulate cyclooxygenase activity (Salvemini et al, 1993).…”
Section: Discussionmentioning
confidence: 99%